2017
DOI: 10.11646/zootaxa.4347.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Annotated Checklist of Tingidae (Hemiptera: Heteroptera) in Turkey with new records for the faunas of Europe and Turkish Thrace

Abstract: In this study, all the so far manuscripts on Tingidae fauna in Turkey has been revised and adults samples from the family Tingidae (Hemiptera: Heteroptera) were collected from different localities in Anatolia and Thrace of Turkey and an annotated checklist of Tingidae occurring is presented. As a results of this study, of Tingidae fauna from Turkey stated that it consists of 78 species has revealed that the number of species is 88 species and 1 subspecies. Nine species and subspecies, Catoplatus horvathi (Puto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 610 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…In 2003, OLB was recorded in Turkey for the first time in the province of Bolu and then in the provinces of Düzce, Zonguldak, Sakarya, Kocaeli, Eskişehir, Ankara, Çankırı and Bilecik [23,24]. Subsequent research in Turkey led to the conclusion that the species has infected 28.000 km 2 of territory [9,25] and is now listed as a permanently monitored invasive species [26,27].…”
Section: The Chronology Of Olb Spread In Europementioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, OLB was recorded in Turkey for the first time in the province of Bolu and then in the provinces of Düzce, Zonguldak, Sakarya, Kocaeli, Eskişehir, Ankara, Çankırı and Bilecik [23,24]. Subsequent research in Turkey led to the conclusion that the species has infected 28.000 km 2 of territory [9,25] and is now listed as a permanently monitored invasive species [26,27].…”
Section: The Chronology Of Olb Spread In Europementioning
confidence: 99%
“…From 2016, was reported in other European countries: Albania, Bosnia and Herzegovina, Greece and Ukraine [48,[50][51][52][53][54]. [19,20]; 2002-Switzerland [21,22]; 2003-Turkey [9,23,24,[25][26][27][28]; 2005-Iran [28]; 2009-Poland [29]; 2012-Bulgaria [30,31]; 2013-Hungary [32,[34][35][36][37]; 2013-Croația [39]; 2013-Serbia [40][41][42]; 2015-Russia [24,[43][44][45][46][47]; 2015-Romania [52,62,64,65,[67][68][69][70]; 2016-Albania, Bosnia and Herzegovina, Greece and Ukraine [48,50,51,[53][54]; 2017...…”
Section: The Chronology Of Olb Spread In Europementioning
confidence: 99%
“…The recent studies in Türkiye revealed presence of 14 species from nine genera of Asopinae, 125 species from 39 genera of Pentatominae, one species from one genus of Phyllocephalinae and 34 species from 12 genera of Podopinae. Among these species, the type localities of 37 species, of which 15 are endemic, from 16 genera of Pentatomidae were given in Türkiye (Lodos et al, 1978(Lodos et al, , 1998Önder et al, 1981, 1984, 2006Lodos & Önder, 1983;Ahmad & Önder, 1990;Belousova, 1999;Fent & Aktaç, 1999;Tezcan & Önder, 1999Tezcan & Önder, , 2003Awad, 2000;Awad & Pehlivan, 2001;Beyaz & Tezcan, 2002;Kıvan, 2004;Kıyak et al, 2004Kıyak et al, , 2019Kment & Jindra, 2005;Özgen et al, 2005a,b;Bolu et al, 2006;Fent & Aktaç, 2007;Külekçi et al, 2009;, 2015, 2017Fent, 2010;Fent et al, 2010;Matocq et al, 2014;Yazıcı et al, 2014;Çerçi & Koçak, 2017;Çerçi & Gözüaçık, 2019;Çerçi, 2021;Çerçi & Özgen, 2021;Fent & Dursun, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although a monograph and a catalog of the Palaearctic Nabidae were published by Kerzhner (1996), and a monograph of the species of Western European and northwest Africa was published by Péricart (1987), knowledge about the Nabide fauna of Türkiye remains scarce. The knowledge of the Nabidae species of Türkiye is scattered in various papers (such as Reuter 1890;Horváth 1918;Puton 1892;Kiritshenko 1918, Hoberlandt 1956, Onder et al 1981, 1983Erbay 1986;Alaoğlu and Ozbek 1987;Gençer et al 2004;Özsemerci 2007;Abacigil et al 2010;Tezcan et al 2010;Dursun 2011;Yıldırım et al 2013;Matocq et al 2014;Asal 2015;Dursun and Fent 2015;Kuçukbasmacı and Kıyak 2015;Dirik and Kıvan 2016;Çerçi et al 2018;Ayaz 2019;Bolu 2019;Şahin 2019;Ali et al 2020;Karapınar and Sertkaya 2020;Maral et al 2020;Çerçi and Tezcan 2021;Ozgen et al 2021;Yazıcı 2022a;Yazıcı 2022b). Erbay (1986), an unpublished master's thesis, remains to be the only study that solely focuses on the Nabidae fauna of the entire Türkiye.…”
Section: Introductionmentioning
confidence: 99%